Evaluation of Wild Birds in the main Campus of Usmanu Danfodiyo University Sokoto, Sokoto State Nigeria (2021)
A re-evaluation study was conducted after eight years of the initial survey to find out the distribution and diversity of avifauna concerning land use types in the main campus of Usmanu Danfodiyo University Sokoto. This was carried out to serve as a follow-up to a survey carried out in 2011 in the study area. Reevaluation of species diversity is important in conservation as it gives more information on habitat conditions which is necessary for drawing conservation strategies. The study area was stratified into the major land-use types which are Residential, Farmland, Administrative, and Wetland areas. The line transect method was used to collect data on bird abundance and distribution. The Simpson index of diversity (SID) was used to determine species diversity between habitat types whereas the Shannon-Weiner diversity index (H) was used to determine species diversity across the entire area. On the other hand, the Equitability index of Evenness (EH) was used to determine evenness in the distribution of avifauna across the entire area. A total of 3183 birds belonging to 23 families and 44 species were recorded. Out of these numbers, 1037(32.58%) were recorded in a residential area, a total of 519 birds (16.31%) were recorded in administrative areas, farmland recorded 1556 birds (48.88%), and wetland areas recorded 71 birds (2.23%). The diversity index ranges from 0.45-0.77 with the highest being administrative areas and the lowest being wetland. The Shannon-Weiner diversity index was 2.35 which indicates considerable diversity across the area. Therefore, efforts should be directed towards conserving the habitats and making communities realize the importance of avian species.